Relationship between External Environment, Internal Conditions, and Digital Transformation from the Perspective of Synergetics. (5th May 2022) - Luo, Xiaowen; Yu, Shun-Chi
Abstract : As the digital technologies develop, traditional pharmaceutical enterprises have also begun the exploration of digital transformation (DT). Previous studies mainly focused on the technology application, strategy, performance, and leadership of digital in manufacturing enterprises and small- and medium-sized enterprises (SMEs), and more qualitative methods were used. However, few researchers systematically investigated the impact mechanism of pharmaceutical enterprises' DT. The purpose of this study is to analyze the influencing factors of Chinese pharmaceutical enterprises' DT by constructing the structural equation model (SEM) based on synergetics. This study shows that the influencing factors of pharmaceutical enterprises' DT include the external environment (customer needs, market competition, government policy, and digital technology) and internal conditions (digital strategy, leadership, and organization capability). The theoretical innovation of this study is to explore the synergistic effect of external environment and internal conditions on DT and put forward that the internal conditions play mediating role in the external environment and DT. Customer needs and digital strategies have great impacts on pharmaceutical enterprises' DT. Therefore, this study finds the main influencing factors, which are helpful in promoting pharmaceutical enterprises' DT.